Development of a Performance Visualization Model of Basic Life Support Training with Feedback Devices for Mobile Application - Navadon Khunlertgit (2018)
© 2018 IEEE. Sudden cardiac arrest is one of the most life-threatening situations. The chance of survival from this emergency increases if the victims receive early basic life support (BLS) including cardiopulmonary resuscitation (CPR) and, if available, defibrillation using automated external defibrillator (AED). This emergency occurs mostly out-of-hospital. Consequently, lay rescuers are the first to react before medical personnel arrives. BLS training is one of the keys providing readiness for bystanders which lead to improving cardiac arrest outcome. Use of feedback devices during BLS training has been shown to improve the performance of learners. Despite the fact that there is a large number of applications in the market aiming to support BLS training, surprisingly, none of them is designed specifically to illustrate data from feedback devices and follow the standard guidelines. This paper discusses the development of a performance visualization model for BLS training with the use of sensor-embedded CPR manikin and AED trainer. The proposed model covers all aspects of BLS training which allow real-time monitoring and assessing the quality of the training. To evaluate the proposed model, an Android application has been implemented and tested in actual BLS training sessions. The prototype demonstrates the potential of using the proposed model to design a mobile application for high-quality BLS training. Total of 23 certified instructors who used the application was asked to complete perceived usability test. The results of the questionnaire indicate that the proposed model has fulfilled in both usefulness and ease of use.